EVALUATION OF NEWLY DESIGNED ISATIN DERIVATIVES AGAINST VARIOUS BACTERIAL SPECIES - SAHU, JYOTI; NIVEDITA, JE RACHEL; KUMAR PATEL, PUSHPENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The main objective of the present research is to develop new isatin derivatives and evaluate their antibacterial properties. Methods: In this research article, some new spiro derivatives of isatin were synthesized by two different pathways. The chalcones were prepared by the reaction of different acetophenones and isatins through base-catalyzed condensation followed by the addition of acid. The compounds have been characterized by UV-Vis, FT-IR, 1H- Nuclear magnetic resonance (NMR), 13C-NMR, and Mass spectra. Results: It was found that the compounds exhibited moderate to significant antibacterial action against four various bacterial strains, that is, Gram-negative Klebsiella pneumoniae and Escherichia coli, Gram-positive Bacillus subtilis, and Staphylococcus aureus. The action of all compounds was compared with standard drug, that is, Streptomycin. Conclusion: It was concluded that all synthesized isatin derivatives are useful for giving antibacterial responses for one or other bacterial strains. Their action was compared with the standard drug and found that ISP1 showed a response that was almost the same as streptomycin’s effects against Salmonella typhi.